The Effects of Green Open Spaces on Microclimate and Thermal Comfort in Three Integrated Campus in Yogyakarta, Indonesia - Ambarwati, Nurwidya; Faida, Lies Rahayu Wijayanti; Marhaento, Hero (Department of Urban and Regional Planning, Diponegoro University, 2023)
This study aims to assess the effect of green open space (GOS) on the microclimate and thermal comfort in three integrated campuses namely Universitas Gadjah Mada (UGM), Universitas Muhammadiyah Yogyakarta (UMY), and Universitas Pembangunan Nasional (UPN) Veteran. In order to achieve the research objective, three main steps were conducted. First, we mapped the GOS area and density of the three integrated campuses using a high-resolution satellite imagery. Second, three microclimate parameters such as air temperature, relative humidity, and wind speed were measured to each detected green spaces in the morning (08:00 am), at noon (01:00 pm), and afternoon (5:00 pm). Subsequently, the results of microclimate measurements were used to calculate the level of thermal comfort using Thermal Humidity Index (THI) method. Third, we carried out statistical analysis to investigate the correlation between the distribution and the density of GOS and the microclimate conditions. The results showed that a negative (-) correlation occurred between the pattern and density of GOS with temperature and wind speed indicating that clustered GOS significantly reduces the air temperature as well as the wind speed. On the contrary, the relative humidity has been increased. UPN campus has the highest temperature and wind speed and the lowest humidity among other campuses. According to the results of THI, a 100% of the UPN areas are uncomfortable, while at UGM and UMY 42,08% and 11,28% of their area are uncomfortable, respectively. This study found that the existence of GOS has an effect on microclimate depending on pattern and density.